User Experience of Creativity Support Tools – A Literature Review in a Management Context - Sengewald, Timon; Roth, Angela (15th International Conference on Wirtschaftsinformatik, 2020)
Creativity Support Tools or Creativity Support Systems are a well-studied subject in the research of computer science and information systems. Whether the User Experience of Creativity Support Tools or Creativity Support Systems has been likewise sufficiently researched, shall be examined. A systematic literature search was conducted to investigate the current state of scientific literature. This review provides a brief overview of open and superfluous research areas in the field of User Experience for the development of Creativity Support Tools for business or management purposes. A total of 19 papers were selected and coded, sorted to concepts and assigned to the various phases of the creative process. The results of the analysis have shown that there is a need for further research in this field.<br
Keywords: creativity support tools; creativity support systems; user experience